1988
DOI: 10.1212/wnl.38.7.1133
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Creutzfeldt‐Jakob disease discovered at autopsy in a human growth hormone recipient

Abstract: An adolescent girl with idiopathic hypothalamic dysfunction and hypopituitarism was treated with human growth hormone between 1969 and 1979, dying of parainfluenza pneumonia 2 months after her last hormone treatment. Although she had no signs of progressive neurologic disease, reexamination of autopsy material revealed a focus of spongiform change and astrogliosis in the corpus striatum. Thus, this growth hormone recipient, who died of intercurrent infection, was unexpectedly found to be in an early, preclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The potential for such cross-infection is underlined by the report of preclinical CJD in a recipient of human growth hormone. 22 The discovery of a biological marker for such cases remains an important objective and might allow a better understanding of the currently unexplained epidemiology of Creutzfeldt-Jakob disease.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for such cross-infection is underlined by the report of preclinical CJD in a recipient of human growth hormone. 22 The discovery of a biological marker for such cases remains an important objective and might allow a better understanding of the currently unexplained epidemiology of Creutzfeldt-Jakob disease.…”
Section: Discussionmentioning
confidence: 99%
“…Two different experimental rodent models have repeatedly documented low levels of buffy coat infectivity [40,41], and a third rodent model comparing scrapie inoculation of intact and transected sciatic nerve suggested hematogenous rather than neural invasion of the brain [50]. A human growth hormone patient who died of pneumonia without any neurological symptoms was found to have neuropathological changes of CJD limited to the hypothalamus, which is not the area that would be predicted if neuroinvasion had proceeded along nervous pathways originating at or around the usual hormone inoculation site of the lateral thigh [51]. Furthermore, the only plausible explanation for the presence of infectivity in many different bodily tissues of humans and animals with TSE is that there is, at some point during its evolution, a 'viremic' (or 'prionemic') phase of disease.…”
Section: Therapeutic Barricadesmentioning
confidence: 99%
“…It had been suggested that those individuals treated by growth hormone prepared using column chromatography might be less at risk, but two HgH recipients in France, who received only this type of growth hormone, have now developed CJD (3). The uncertainties about risk complicate the counselling of at-risk individuals, who nonetheless should be advised not to act as blood or organ donors, particularly in view of the possibility of subclinical disease (22).…”
Section: Iatrogenic Transmission Is Rare and Cannot Be Invoked As An mentioning
confidence: 99%